基于Pro/E的越野车托森差速器参数化设计 - 王欢; 孙传琼; 刘雍德; 李善杰 (Jixie chuandong)
The Torsen differential increase torque ratio and automatically adjust torque distribution according to the change of rotation speed difference by direct and inverse two pairs of worm gear and the worm driving with the characteristics of high friction and low efficiency,the ground through performance of off-road vehicle is improved.The 3D parametric entity modeling of the main component such as spur gear,worm and worm gear and spiral bevel gear for worm gear-limited differential is completed based on Pro/E,the parametric design of Torsen differential for off-road vehicle is realized.The design personnel repeated labor is reduced and the design efficiency is improved.